IMPLEMENTASI PERATURAN DAERAH KOTA PONTIANAK NOMOR 04 TAHUN 2011 TENTANG RETRIBUSI JASA UMUM DI PASAR KEMUNING KECAMATAN PONTIANAK KOTA - Aulia Nur Fateha; Pudjianto Pudjianto; Joko Triyono (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2022)
This study aims to describe and analyze the process of implementing the Pontianak City Regional Regulation Number 4 of 2011 concerning Public Service Fees, especially in dealing with market service fees at Kemuning Market, Municipal Pontianak Sub-District. The method used in this research was descriptive with a qualitative approach. This study used the theory of implementation proposed by Charles O’ John (in Widodo, 2008: 89) which consists of: 1) Organization, the conclusion is the process of implementing the Regional Regulation which is the implementer of the policy, in terms of quantity, the Office of Cooperatives, Micro Enterprises, and Trade still lacks the human resources especially the officers that collect market service fees. 2) Interpretation, the conclusion is that in understanding the purpose and policy of this market service fees, understanding the policy targets, namely vendors, has been channeled through socialization which must be carried out regularly and periodically. 3) Application stage, the conclusion is that the collection of market service fees by the Office of Cooperatives, Micro Enterprises, and Trade is carried out every day by appointed officers. The recommendations from this research are among others, that the Office of Cooperatives, Micro Enterprises, and Trade should increase its human resources, especially the fee collectors; the socialization should emphasize more on complete interpretation; and the fee determination needs to be re-evaluated.Keywords : Application, Interpretation, Organization.